The stress response neuropeptide CRF increases amyloid‐β production by regulating γ‐secretase activity. (11th May 2015) - Park, Hyo‐Jin; Ran, Yong; Jung, Joo In; Holmes, Oliver; Price, Ashleigh R; Smithson, Lisa; Ceballos‐Diaz, Carolina; Han, Chul; Wolfe, Michael S; Daaka, Yehia; Ryabinin, Andrey E; Kim, Seong‐Hun; et al.
Abstract The biological underpinnings linking stress to Alzheimer's disease (AD) risk are poorly understood. We investigated how corticotrophin releasing factor (CRF), a critical stress response mediator, influences amyloid‐β (Aβ) production. In cells, CRF treatment increases Aβ production and triggers CRF receptor 1 (CRFR1) and γ‐secretase internalization. Co‐immunoprecipitation studies establish that γ‐secretase associates with CRFR1; this is mediated by β‐arrestin binding motifs. Additionally, CRFR1 and γ‐secretase co‐localize in lipid raft fractions, with increased γ‐secretase accumulation upon CRF treatment. CRF treatment also increases γ‐secretase activity in vitro, revealing a second, receptor‐independent mechanism of action. CRF is the first endogenous neuropeptide that can be shown to directly modulate γ‐secretase activity. Unexpectedly, CRFR1 antagonists also increased Aβ. These data collectively link CRF to increased Aβ through γ‐secretase and provide mechanistic insight into how stress may increase AD risk. They also suggest that direct targeting of CRF might be necessary to effectively modulate this pathway for therapeutic benefit in AD, as CRFR1 antagonists increase Aβ and in some cases preferentially increase Aβ42 via complex effects on γ‐secretase.